HUBUNGAN PENGETAHUAN DAN SOSIAL BUDAYA TERHADAP MOTIVASI IBU MENGIKUTI IMUNISASI MEASLES RUBELLADI DESA TARAI BANGUN WILAYAH KERJA PUSKESMAS TAMBANG - Afiah Afiah; Mistadiana Mistadiana (Universitas Pahlawan, 2019)
The incidence of measles in Indonesia is increasing every year from year to year. Rubella is a public health problem that requires effective prevention. Surveillance data for the past 5 years shows that 70% of Rubella cases occur in the age group